Case Report: Labial Veneer All Porcelain With Press Method For Improving Aesthetic On Patient With Central Diastema Case - Endang Prawesthi; Moh Hasan (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Patients with central diastema disorders often feel shame and less of confident. The disorder can be repaired by a Labial veneer restoration. This restoration is an improvement in the form of a layer on the labial surface of the tooth selected because it gives satisfactory aesthetic results and maintains the tooth structure. At this time, the method of fabricating labial veneer all porcelain growing rapidly, such as making labial veneer all porcelain with base layer using press method like all porcelain E-max press. This paper aims to determine the stages and problem solving of the difficulties that arise in the procedure of fabricating labial veneer all porcelain with the basic layer of labial veneer using press method. The method is based on working model done in dental laboratory, starting from work model preparation, wax contouring (wax up), Sprueing, Investing, Preheating, Pressing, Divesting, Cutting sprue and Build-up porcelain. Results obtained from making this labial veneer all porcelain is a tightly closed diastema that forms a contact of the field, smooth and glossy surface and good aesthetic.